Inclusion of equity in economic analyses of public health policies: systematic review and future directions. (12th September 2017) - Lal, Anita; Moodie, Marjory; Peeters, Anna; Carter, Rob
Abstract: Objectives : To assess current approaches to inclusion of equity in economic analysis of public health interventions and to recommend best approaches and future directions. Methods : We conducted a systematic review of studies that have used socioeconomic position (SEP) in cost‐effectiveness analyses. Studies were identified using MedLine, EconLit and HEED and were evaluated based on their SEP specific inputs and methods of quantification of the health and financial inequalities. Results : Twenty‐nine relevant studies were identified. The majority of studies comparing two or more interventions left interpretation of the size of the health and financial inequality differences to the reader. Newer approaches include: i) use of health inequality measures to quantify health inequalities; ii) inclusion of financial impacts, such as out‐of‐pocket expenditures; and iii) use of equity weights. The challenge with these approaches is presenting results that policy makers can easily interpret. Conclusions : Using CEA techniques to generate new information about the health equity implications of alternative policy options has not been widely used, but should be considered to inform future decision making. Implications for public health : Inclusion of equity in economic analysis would facilitate a more nuanced comparison of interventions in relation to efficiency, equity and financial impact.